Selected Abstracts of the 22nd European Neonatal Workshop; Siena (Italy); Carthusia Pontiniani; June 15-18, 2014 - - (Hygeia Press di Corridori Marinella, 2014)
Selected Abstracts of the 22nd European Neonatal Workshop • Siena (Italy) • Carthusia Pontiniani • June 15th-18th, 2014 Guest Editor: Giuseppe Buonocore ABS 1. Incidence and risk factors of intraventricular hemorrhage (IVH) in infants less than 32 weeks of gestation • G. Mitsiakos, A. Papageorgiou; Montreal (Canada) ABS 2. Cord blood concentrations of the myokine irisin in fetal macrosomia • D.D. Briana, T. Boutsikou, M. Boutsikou, S. Baka, A. Marmarinos, D. Hassiakos, D. Gourgiotis, A. Malamitsi-Puchner; Athens (Greece) ABS 3. Asynchronous chest compressions improve survival in a neonatal piglet model of asphyxial cardiac arrest • N. Iacovidou, A. Aggelina, A. Papalois, A. Douvanas, P. Pliatsika, T. Xanthos; Athens (Greece) ABS 4. Human cytomegalovirus (CMV) congenital infection. Implementation of a screening program during pregnancy • I. Dorronsoro, M. Lopez-Azorin, M. Caballero, J. García-Flores, M. Recio, A. Pellicer, F. Cabañas; Madrid (Spain) ABS 5. Steps forward the BiAR-COH method in autoregulation analysis: assessment of causality • J. Riera, F. Cabañas, J.J. Serrano, M.C. Bravo, P. López-Ortego, L. Sánchez, R. Madero, A. Pellicer; Madrid and Zaragoza (Spain) ABS 6. Comparison of delivery room care in three countries: There are many ways of skinning a cat • S. Walter, B. Simma, J. van Vonderen, A.B. te Pas, H. Küster; Göttingen (Germany), Feldkirch (Austria) and Leiden (The Netherlands) ABS 7. Diaphragmatic function in convalescent preterm infants with chronic lung disease • G. Dimitriou, A. Vervenioti, S. Fouzas, P. Pelekouda; Patras (Greece) ABS 8. Stem/progenitors in the newborn kidney: an undiscovered resource to prevent kidney failure later in life? • G. Faa, C. Gerosa, A. Sanna, M. Puddu, D. Fanni, V. Fanos; Cagliari (Italy) ABS 9. Placental histological patterns and oxidative stress in the offspring • S. Perrone, S. Negro, M.S. Cori, M.G. Alagna, P. Toti, M.S. Toti, C. Felici, M. Longini, M.L. Tataranno, G. Buonocore; Siena (Italy) ABS 10. Placental histological patterns and neonatal follow-up • S. Perrone, S. Negro, M.G. Alagna, M.S. Cori, M.S. Toti, P. Toti, G. Turrisi, M.L. Tataranno, G. Buonocore; Siena (Italy) ABS 11. Foundling infants in the centuries • L. Cataldi, M.G. Gregorio; Rome and Cagliari (Italy) ABS 12. Prospective validation of vancomycin dosing is needed and should be driven by GFR maturation modelling • K. Allegaert; Leuven (Belgium) ABS 13. Gestational pathology and the success of breastfeeding • A. Pereira, D. Morgado; Braga (Portugal) ABS 14. Respiratory morbidity in very preterm infants in the first two years of life • M. Ferreira, M.F. Magalhães, G. Rocha, H. Guimarães; Porto (Portugal) ABS 15. Evidence of transitory hypo-alpha-1-antitrypsinaemia within the first months of life • H. Varendi, E. Kallas, J. Kuld, P. Külasepp, M.A. Vals, M.K. Uprus, L. Saare, S. Leedo; Tartu (Estonia) ABS 16. Neurological morbidity in very preterm preschool children • M. Madureira, A. Vilan, S. Almeida, F. Flor de Lima, A. Martins, H. Guimarães; Porto (Portugal)